Targeting Purinergic Receptor P2RX1 Modulates Intestinal Microbiota and Alleviates Inflammation in Colitis - Wang, Xu; Yuan, Xiao; Su, Yuting; Hu, Jing; Ji, Qian; Fu, Shengqiao; Li, Rongkun; Hu, Lipeng; Dai, Chunhua (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD) remains one of the most prevalent gastrointestinal diseases worldwide. Purinergic signaling has emerged as a promising therapeutic target of inflammation-associated diseases. However, little is known about the specific roles of purinergic receptors in IBD. In the present study, expression profile of purinergic receptors was screened in the public Gene Expression Omnibus (GEO) datasets, and we found that expression of P2RX1 was significantly upregulated in inflamed colon tissues. Then, purinergic receptor P2RX1 was genetically ablated in the background of C57BL/6 mice and dextran sulfate sodium (DSS) was used to induce mice colitis. RNA sequencing of colon tissues showed that ablation of P2RX1 accomplished the inflammation conditions in DSS-induced mice colitis. 16S ribosomal DNA sequencing revealed major differences of intestinal microbiota between WT and P2RX1 ablated mice. Functional metagenomics prediction indicated that indole alkaloid biogenesis pathway was the upregulated in P2RX1 gene ablated mice. Further studies revealed that microbiota metabolites (indole alkaloid)-involved aryl hydrocarbon receptor (AhR)/IL-22 axis accounts for the beneficial effects of P2RX1 ablation. Finally, we found that a specific P2RX1 inhibitor succeed to improve the therapeutic efficiency of anti-TNF-α therapy in DSS-induced mice colitis. Therefore, our study suggest that targeting purinergic receptor P2RX1 may provide novel therapeutic strategy for IBD.